Managing mental health problem among domestic violence victims in Selangor using the theory of hisbah and Al-Ghazali approach - Zuraimy Ali,; Noraini Ismail,; Khadher Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The COVID-19 pandemic that is plaguing the country since 2019 gives a huge impact on the world including Malaysia. The pandemic also affects Malaysia’s economy, society, and prosperity. This pandemic had also caused an increase in cases of domestic violence in this country. The Movement Control Order (MCO) that was implemented by the Malaysian government has caused the community to be confined and experience pressure from various angles such as abuse and domestic violence. Mental health has become a headline issue in Malaysia and many efforts have been made to create the awareness on mental health care especially during COVID-19. The uncertainty of COVID-19 as a result of restrictions, physical confinement, and other procedural standards being implemented has caused economic turmoil and increased the risk of mental health problems. Qualitative analysis had been used in this study to enable the researchers to develop a new model of hisbah integration dan al-Ghazali theory in preventing the issue of domestic violence towards four domestic violence victims in Selangor, Malaysia. A face-to-face interview session was conducted to obtain the findings. The result of the analysis demonstrated that the practise of hisbah theory on the development of spirituality has helped in curing domestic violence by reducing pressure and anxiety. This shows that by only performing the daily five times prayer is the most preferable action by the domestic violence victims. However, the rest of the hisbah elements and al Ghazali approach are not effective to them.